Natalizumab in Multiple Sclerosis: Long-Term Management - Clerico, Marinella (Int J Mol Sci, 2017)
Natalizumab is a monoclonal antibody highly effective in the treatment of relapsing remitting multiple sclerosis (RRMS) patients. Despite its effectiveness, there are growing concerns regarding the risk of progressive multifocal leukoencephalopathy (PML), a brain infection caused by John Cunningham virus (JCV), particularly after 24 doses and in patients who previously received immunosuppressive drugs. Long-term natalizumab treated, immunosuppressive-pretreated, and JCV antibody-positive patients are asked to rediscuss natalizumab continuation or withdrawal after 24 doses. Until now, there has not been a clear strategy that should be followed to avoid PML risk and in parallel reduce clinical and radiological rebound activity. In this review, we analyzed the results of clinical trials and case reports in relation to the following situations: natalizumab continuation, natalizumab discontinuation followed by full therapeutic suspension or switch to other first or second line MS treatments. Quitting all MS treatment after natalizumab increases MS activity occurrence. The results regarding the therapeutic switch are not homogeneous, so at the moment there are no established guidelines regarding natalizumab treatment after 24 administrations; the choice is currently based on the professional experience of the neurologist, and on patients’ clinical features and preferences.